2022
DOI: 10.2147/jmdh.s367241
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Microvascular Complications Among Type 2 Diabetic Patients Using Cox Proportional Hazards Models: A Cohort Study in Tabuk Saudi Arabia

Abstract: The burden of type 2 diabetes (T2D) is high in Saudi Arabia, but data related to its complications are limited. This study aimed to determine the incidence of microvascular complications caused by T2D and evaluate the impact of the associated risk factors. Patients and Methods: This retrospective cohort study was conducted at two military hospitals in Tabuk, Saudi Arabia. Data on the socio-demographics, glycaemic profile, blood lipid indices, duration of T2D, and associated microvascular complications were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
3
3
1
Order By: Relevance
“…Furthermore, in this study, the risk of diabetic microvascular complications was higher in patients with a T2DM duration ≥ 5 years. The finding is in accordance with the studies conducted in Ethiopia, Nigeria, Saudi Arabia, China, and Ireland ( 14 , 16 , 17 , 20 , 24 ). Moreover, the finding that the risk of diabetic microvascular complications was higher in patients with T2DM whose total cholesterol ≥ 200 mg/dl is consistent with previous studies done in Saudi Arabia and China ( 14 , 17 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, in this study, the risk of diabetic microvascular complications was higher in patients with a T2DM duration ≥ 5 years. The finding is in accordance with the studies conducted in Ethiopia, Nigeria, Saudi Arabia, China, and Ireland ( 14 , 16 , 17 , 20 , 24 ). Moreover, the finding that the risk of diabetic microvascular complications was higher in patients with T2DM whose total cholesterol ≥ 200 mg/dl is consistent with previous studies done in Saudi Arabia and China ( 14 , 17 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, the finding was higher than the finding of studies from Northern Ethiopia 19.5%, and Chandigarh, India 18.04% ( 13 , 21 ). The finding of this study was lower than the finding of the studies conducted in Jimma, Ethiopia 41.5%, Dessie, Ethiopia 37.9%, Gondar, Ethiopia 31.33%, Ayder, Ethiopia 42.6%, Jos, Nigeria 47.8%, Tabuk, Saudi Arabia 34.3%, Doha, Qatar 48.4%, South India 52.1%, Tianjin, China 34.5%, and Ningbo, China 57.5% ( 14 17 , 19 , 20 , 23 26 ). This discrepancy might be due to differences in diagnostic methods or criteria, sample size, and healthcare systems.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…This is not uncommon; as such variations have been reported in previous studies. [ 26 , 33 ] Also, the cross-sectional study design could contribute to this, as these risk factors were assessed once.…”
Section: Discussionmentioning
confidence: 99%
“…This goes with a study from Saudi Arabia, where diabetic retinopathy was the most frequent microvascular complication, followed by neuropathy and, lastly, nephropathy. [ 33 ] Nevertheless, different results from the Indian population showed that peripheral neuropathy (44.9%) was the most frequent complication, followed by nephropathy (12.1%). [ 34 ] A Chinese study in patients with diabetes found the prevalence of neuropathy, retinopathy, and kidney disease to be 23.5%, 17.4%, and 10.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%